2014
DOI: 10.1177/0363546514561004
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Repair of Partial-Thickness and Small Full-Thickness Rotator Cuff Tears

Abstract: The high-grade partial-thickness rotator cuff tears showed more severe tendinosis compared with the small full-thickness tears in this study. Contrary to previous impressions that tear size or fatty infiltration is the factor that most influences healing, tendinosis severity assessed by preoperative MRI was the only factor associated with failure to heal, given the numbers available for analysis, in patients with partial-thickness and small full-thickness rotator cuff tears. Surgeons should pay more attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 64 publications
(83 reference statements)
1
67
0
Order By: Relevance
“…A relatively small tendon tear size within our study cohort is partially explained by our study protocol with selective inclusion of isolated supraspinatus tears. In line with other previous studies, preoperative MRI‐based parameters did not significantly predict postoperative shoulder function and tendon retear within our cohort . However, since it was not a main aspect of our study to evaluate the previously reported conventional MRI‐based predictors, we cannot rule out that we missed predictive effects due to our small cohort size and herefrom resulting low statistical power for the expected moderate‐to‐weak effects of these parameters.…”
Section: Discussionsupporting
confidence: 77%
“…A relatively small tendon tear size within our study cohort is partially explained by our study protocol with selective inclusion of isolated supraspinatus tears. In line with other previous studies, preoperative MRI‐based parameters did not significantly predict postoperative shoulder function and tendon retear within our cohort . However, since it was not a main aspect of our study to evaluate the previously reported conventional MRI‐based predictors, we cannot rule out that we missed predictive effects due to our small cohort size and herefrom resulting low statistical power for the expected moderate‐to‐weak effects of these parameters.…”
Section: Discussionsupporting
confidence: 77%
“…The study included a total of 68 patients, 38 patients with anterior greater tubercle cysts, taking into consideration the similar comparative retrospective studies performed in the literature. 1,15,[19][20][21]…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been supported by the imaging literature as well. Recently, in the setting of partial‐thickness and small full‐thickness tears, Chung et al described an association between the severity of tendinosis on MRI and repair failure that appeared more predictive than traditional measures of tear size and muscle atrophy, although their sample size was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been supported by the imaging literature as well. Recently, in the setting of partialthickness and small full-thickness tears, Chung et al 21 described an association between the severity of tendinosis on MRI and repair failure that appeared more predictive than traditional measures of tear size and muscle atrophy, although their sample size was relatively small. Nevertheless, although morphologic assessment clearly provides information on characteristics that indirectly reflect tendon quality (such as the degree of Hou et al-Elastography of the Rotator Cuff Tendon tendinosis), it does not directly capture the mechanical properties of the tendon and may fail to predict the tendon response to a tensile load.…”
Section: Importance Of Tendon Qualitymentioning
confidence: 99%